2003
DOI: 10.1109/jsac.2003.810297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MIMO antenna configurations in picocell and microcell environments

Abstract: This paper presents the results achieved with a dualpolarized multiple-input multiple-output (MIMO) measurement system in the 2 GHz range. Results from continuous measurement routes were used in evaluating and comparing different MIMO antenna configurations. Different pattern and polarization diversity possibilities were studied using two methods: elements were selected from the antenna arrays used in measurements, and as another option, in the mobile station the incident waves were estimated and used in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Another measurement results in micro-and pico-cell show the channel capacity of MIMO systems with dual-polarized antenna elements are 14% higher than that with twicenumbered single-polarized antennas (Sulonen et al, 2003). Similar results are also obtained (Erceg et al, 2006).…”
Section: Dual-polarized Antennasupporting
confidence: 64%
“…Another measurement results in micro-and pico-cell show the channel capacity of MIMO systems with dual-polarized antenna elements are 14% higher than that with twicenumbered single-polarized antennas (Sulonen et al, 2003). Similar results are also obtained (Erceg et al, 2006).…”
Section: Dual-polarized Antennasupporting
confidence: 64%
“…On the base station side, link capacity can be improved by employing multiple antennas without space restrictions [6]. In contrast, compact terminal antennas are strictly limited in size.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of vehicular-based MIMO channels were reported in [9][10][11][12][13][14][15][16][17], where the MIMO channels were measured using systems with one fixed endpoint and one vehicular-based endpoint. Lower mobility outdoor measurement campaigns have been performed using a mobile transmitter or receiver mounted on a trolley, pushed at walking speed, for example, [18][19][20]. The fixed wireless outdoor International Journal of Antennas and Propagation MIMO channel has also been investigated in urban environments, see, for example, [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%